Landasan politik dan hukum pendidikan islam - Ain, Failla Aylana (Maliki Interdisciplinary Journal, 2025)
In essence, the creation of law is a function of implementing statutory orders established by legislative bodies. Legislation to resolve a case being examined by a judge includes the executive branch, which creates legal regulations, either alone or in conjunction with the legislative branch. This constitutes the enforcement of the legal regulations themselves. Under the principle of separation of powers, lawmaking is a constitutional function carried out by the executive, legislative, and judicial branches, both written and unwritten. This is solely the authority of the legislative body, a function not shared by other bodies. Meanwhile, under the concept of the division of powers, the legislative, executive, and judicial bodies carry out these functions effectively. Therefore, through the creation of legal regulations as a form of implementing legal policy, the legal system must contain regulations that are as neutral as possible and impartial. The law is part of the legal role. In reality, education in Indonesia is currently unequal and there are many disparities, especially between urban and rural areas. Furthermore, numerous violations of regulations continue to occur, resulting in losses for many parties. Therefore, this article discusses laws and policies in the field of education.